Physical performance in Danish elite team handball players - Jensen, K.; Johansen, L.; Larsson, B. (1999)
Physical demands in international handball was evaluated by measuring physical performance of the best players. The best national team (A) compared to younger teams (U, Y), indicate if some physical factors are more important than others. Physiological parameters were measured in 47 A team players, 52 U, and 43 Y, age 24.4±3.5, 19.7±0.8 and 17.9±0.7 years, respectively. Physical performance parameters such as maximal oxygen uptake (VO2max) and maximal treadmill running time (Tmax) were measured in the laboratory. Sprint time over 5 and 30 m (T5m and T30m), Counter-movement jump without load and loaded with half the bodyweight (CMJ and CMJ½BW), shooting velocity in 3 shots: standing, after 3 steps and after a jump (SST, S3S and SJU), and a 30 m shuttle run with increasing speeds between markers until exhaustion (30mshuttle) were measured in the field.